HETEROTROPHIC BACTERIOPLANKTON OF LAKE VISHTYNETSKY, KALININGRAD REGION IN THE SUMMER SEASON OF 2024 (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
In the article the abundance, taxonomic composition and degree of similarity of heterotrophic bacterioplankton communities were determined in Lake Vishtynetsky, Kaliningrad Region. The analysis of abundance, taxonomic composition and degree of similarity of heterotrophic bacterioplankton in a freshwater body allowed us to reveal differences in its composition. We found that the quantitative indices of bacterioplankton varied insignificantly from 0.1·103 CFU/mL to 0.4·103 CFU/mL. Bacterioplankton abundance increased in the central and southern parts of the reservoir.  Comparison of the similarity of bacterioplankton communities using the Czekanowski coefficient in the selected zones revealed a high percentage of similarity between all the studied communities of more than 50%. The distribution of bacterioplankton of this water body is expressed through numerical heterogeneity and different qualitative composition.
Keywords: Lake Vishtynetskoe; bacterioplankton; taxonomic composition